Improving the Quality of Cake Mold Products Through the Integration of Green Manufacturing and Good Manufacturing Practice (GMP) Using the KPI, FMEA, and Fishbone Diagram Approaches: Peningkatan Mutu Produk Cetakan Kue Melalui Integrasi Green Manufacturing dan Good Manufacturing Practice (GMP) Menggunakan Pendekatan KPI, FMEA, dan Fishbone Diagram - Lolyka Dewi Indrasari; Johan Alfian Pradana; Ana Komari; Afiff Yudha Tripariyanto; Venus Khatta S (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2026)
PT. X activities have entered the mid-scale home industry of Cookie cutting production. Where industrial activities are an allocation of 8 hours of work per day. The dominant pollution that occurs is the remnants of slab iron that is perca. The utilization of iron slabs that have not been maximal will cause Environmental hazards. This danger occurs is wasted in the Environment. The purpose of the study is to determine the results of key performance indicators to provide improved good manufacturing with the integration of Fishbone diagrams reviewed from ISO 22000: 2009, ISO 14001:2015, and HACCP. The research stage is to assess aspects of waste, energy usage, and yieldss. Continued to review the proposed green manufacturing improvement using FMEA Integration Fishbone diagram. This research shows that aspects of green manufacturing have qualified ISO 22000:2009, ISO 14001:2015, and HACCP and proposed improvements that are expected to be motivated, intensive monitoring, and maintaining green manufacturing conditions to improve.